Telencephalosynapsis (synencephaly) and rhombencephalosynapsis with posterior fossa ventriculocele (‘Dandy-Walker cyst’): an unusual aberrant syngenetic complex - Sergi, Consolato M.; Hentze, Sabine; Sohn, Christof; Voigtländer, Theda; Jung, Christine; Schmitt, Horst Peter (Brain & development, 1997)
Agenesis of the cerebellar vermis (paleocerebellar agenesis) with fusion of the cerebellar hemispheres (rhombencephalosynapsis) is a rare malformation of the central nervous system (CNS). Its combination with synencephaly (telencephalosynapsis), telencephalic ventricular aplasia, aqueductal atresia and cystic fourth ventricle has not yet been described, as far as we know. Here, were report this combination in a 23-weeks' gestation male fetus who was aborted to a 24-year-old diabetic mother. In this fetus with cerebral and cerebellar hemispheric fusion, vermian agenesis was associated with a Dandy-Walker-like posterior fossa cyst, in spite of the fusion of the hypoplastic cerebellar hemispheres. The CNS malformations were further accompanied by dysmorphic facial stigmata such as unilateral atresia of the external ear, ocular hypertelorism and a broad nasal bridge. Preaxial polydactyly and contractures of the upper limbs were the only associated noncranial abnormalities. Cytogenetic studies revealed a numerically and structurally normal male (46, XY). The malformation complex described in this fetus of a mother with antedating pregnancy diabetes appears to represent a previously undescribed aberrant syngenetic CNS phenotype, some basic teratogenetic aspects of which will be discussed in this paper.